Solvability for a Hadamard-type fractional integral boundary value problem - Xu, Jiafa; Liu, Jie; O'Regan, Donal (Nonlinear Analysis: Modelling and Control, 2023)
In this paper, we study an integral boundary value problem involving a Hadamard-type fractional differential equation. Using fixed point theory and upper-lower solutions, we present some sufficient conditions to obtain existence theorems of positive solutions for the problem. Examples are provided to illustrate our results.
Keywords: Hadamard-type fractional differential equations; integral boundary value problems; positive solutions; fixed point methods; upper-lower solution methods